Attitudes of blood and plasma donors towards biobanking for longitudinal health research - Karlijn F. Joosten; Lotte van Dammen; Eva-Maria Merz; Věra M. J. Novotný; Daphne C. Thijssen-Timmer; Katja van den Hurk (PLoS ONE, 2025)
Background Blood and plasma donations provide a unique opportunity for setting up a biobank. Remainders of donations can be stored together with questionnaire data to allow for longitudinal health research. Insight in the attitude and understanding of potential concerns of donors towards biobanking allows incorporating their perspective in the set-up of biobanks as such. Methods In an online survey in July/August 2021 among 409 Dutch donors, we asked about their attitudes towards the collection and storage of remainders of donations, questionnaires, and DNA, and towards the storage period, data sharing and linkage, and feeding back results and outcomes. Results The overall attitude of participating donors towards biobanking remainders of donations is very positive with 99% indicating willingness to provide their consent and 94% to fill out questionnaires. Most respondents (74%, n = 292/395) would agree to a long-term storage of 30 years. When asked about potential concerns, respondents mostly mentioned personal data security (30%), commercial use of data (11%) and misuse of data (5%). Also, 40% (n = 155/390) showed some hesitance towards the storage of DNA, including 28% (n = 111/390) who would give conditional consent if being informed on for instance DNA utilisation. Finally, the majority would like to receive feedback of research results, and indicated this to contribute to a greater likelihood of biobank participation. Conclusion Our findings show high support among surveyed donors for the storage of donation remainders in a biobank, provided high data security standards and clear communication about data protection measures and usage of biobank data and materials.